Effect of Digital Marketing Capabilities and Blockchain Technology on Organizational Performance and Psychology - Liu, Ying (Frontiers in Psychology, 2022)
Digitalization plays an integral role in the transformation of the Omni structure. This study aims to investigate the effect of digital marketing capabilities (DMCs) and blockchain technology on customer-linking capabilities (CLCs), market-sensing capabilities (MSCs), consumer-brand engagement (CBE), and firm performance in China. The study was quantitative, and a simple random sampling technique was adopted for data collection. Data were collected using a structured questionnaire, 311 questionnaires were distributed, and a 5-point Likert scale was used to collect the data from the respondents who were employed in the Omni structure industries. The research hypothesis was tested using the structural equation modeling (SEM) technique. The results have identified a significant correlation and direct effect between DMCs, CLCs, MSCs, and firm performance. Remarkably, the effect of DMCs on CBE is significant. The mediating effect of MSCs and CLCs is significant between the relationship of DMCs and firm performance. The organization performance in the Omni structure depends on how well the DMCs have been employed. The DMCs influence MSCs, CLCs, and CBE. Henceforth, this study contributes by analyzing the role of DMCs in blockchain technology.